PENGARUH BOOK TAX DIFFERENCE, TINGKAT HUTANG DAN VOLATILITAS ARUS KAS TERHADAP PERSISTENSI LABA (Studi Empiris Pada Perusahaan Consumer Goods Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2017) - B2091171002, ALEXANDER LIYARDI (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2019)
This study aims to analyze the impact of book-tax difference, debt level and cash flow volatility on earnings persistence in consumer goods companies listed on the Indonesia Stock Exchange in the period 2013-2017. The theory apllied in this study is agency theory and positive accounting theory.The research findings indicate that the level of debt has a positive and significant effect on earnings persistence in consumer goods companies listed on the Indonesia Stock Exchange in the period 2013-2017, while the book-tax difference and cash flow volatility do not affect the persistence of earnings. The limitations in this study found that the independent variable under study only had and effect of 6,5%, so the remaining 93,5% was influenced by other factors which could be examined further. Keywords : Book Tax Difference, Debt Level, Cash Flow Volatility and Earning PersistenceDAFTAR PUSTAKABaylock, B., Shevlin,T., & Wilson, R. J. (2012). Tax Avoidance, Large Positive Temporary Book-Tax Differences, and Earnings Persistence. The Accounting Review, 87 (1). 91-120. doi: 0.2308/accr-10158 Fanani, Z. (2010). Analisis Faktor-Faktor Penentu Persistensi Laba. Jurnal Auntansi dan Keuangan Indonesia, 7 (1). 109-123.Ikatan Akuntan Indonesia. (2016). Standar Akuntansi Keuangan Efektif Per 1 Januari 2017. Jakarta: Divisi Penerbit IAI.Jensen, M.C., & Meckling, W. (1976). Theory of the firm: Managerial behavior, agency cost and ownership structure. Journal of Financial Economics, 3. 305-360.Jonas, G. J., & Blanchet, J. (2000). Assesing Quality of Financial Reporting. Accounting Horizons,14 (3). 353-363. doi: 10.2308/acch.2000.14.3.353 Moses, O.D. (1987). Income Smoothing and Incentives: Empirical Tests Using Accounting Changes. The Accounting Review, 62 (2). 358-377. Retrieved from https://www.jstor.org/stable/247931.Penman, S.H., & Zhang, X.J. (2002). Accounting Coservatism, the Quality of Earning and Stock Returns. Working Paper. Persada, A. E., & Martani, D. (2010). Analisis Faktor Yang Mempengaruhi Book Tax Difference Dan Pengaruhnya Terhadap Persistensi Laba. Jurnal Akuntansi dan Keuangan Indonesia, 7 (2). 205-221.Saputra, I.D.G.D. (2003). Penggunaan Rasio Keuangan Sebagai Ukuran Risiko Dalam Menentukan Bid-Ask Spread. Tesis. Universitas Gadjah Mada, Indonesia Scott, W. R. (2009). Financial Accounting Theory. Toronto: Pearson.Sulastri, D. A. (2010). Pengaruh Volatilitas Arus Kas, Volatilitas Penjualan, Besaran Akrul Dan Tingkat Hutang Terhadap Persistensi Laba. Universitang Negeri Padang, Indonesia.Suwardjono. (2008). Teori Akuntansi, Perekayasaan Akuntansi Keuangan. Yogyakarta: BPFE V Watts, R. L., & Zimmerman, J. L. (1990). Positive Accounting Theory : A Ten Year Perspective. The Accounting Review, 65 (1). 131-156. Retrieved from https://www.jstor.org/stable/247931.